Differences in virulence for mice among strains of Mycoplasma pulmonis. - Davidson, M K (1988)
The mouse model of acute murine respiratory mycoplasmosis was used to screen 18 strains of Mycoplasma pulmonis for their ability to establish respiratory infections and produce gross lung lesions in the susceptible C3H/HeN mouse strain. All experiments were designed to minimize host, environmental, and microbial differences to ensure that experimental results would reflect differences in mycoplasmal virulence. There were differences in the 50% infectious dose (range, 3 X 10(2) to greater than 10(7) CFU) and the 50% gross pneumonia dose (range, 10(3) to greater than 10(7) CFU) among the 18 mycoplasmal strains. Only 10 strains (UAB CT, M1, UAB 5782C, UAB 6510, 66, UAB T, UAB 8145D, Nelson C, Peter C, and Negroni) established respiratory infections, and only 2 of the 10 strains (UAB CT and M1) produced gross lung lesions. Strains UAB CT, UAB T, M1, UAB 5782C, and PG34(ASH) were chosen for qualitative and quantitative evaluation of lung lesions in C3H/HeN and C57BL/6N mice. Lesion incidence and severity was dependent on the mycoplasmal strain and the mouse strain. Microscopic lesions varied among mycoplasmal strains and mouse strains in the amount of lymphoid infiltrate, neutrophilic exudate, and consolidation, as well as overall severity. The most virulent strain, UAB CT, produced acute pneumonitis in the 10(7) CFU dosage group and required a threshold dose of 10(3) CFU to consistently produce microscopic lung lesions. These results suggest that M. pulmonis virulence is multifactorial and different strains of mycoplasmas yield disease expressions that differ both qualitatively and quantitatively.